Intestinal Necrosis due to Giant Ovarian Cyst: A Case Report - Ali Duran; Fulay Yilmaz Duran; Fevzi Cengiz; Ozgur Duran (Case Reports in Surgery)
Intestinal pathologies due to ovarian cyst are observed rarely. Although a limited number of cases in neonatal and adolescent periods have been observed, no adult case has been reported in the literature. Two mechanisms are involved in intestinal complications due to ovarian cysts: torsion due to adhesion or compression of giant ovarian mass with a diameter of 9-10 cm. We report here a terminal ileum necrosis case due to compression by an ovarian cyst with 11 × 10 × 7 cm size in an 81-year-old woman.